2000
DOI: 10.1128/jvi.74.21.10055-10062.2000
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Hepatitis C Virus (HCV) and HCV E2 Interactions with CD81 and the Low-Density Lipoprotein Receptor

Abstract: Hepatitis C virus (HCV) or HCV-low-density lipoprotein (LDL) complexes interact with the LDL receptor (LDLr) and the HCV envelope glycoprotein E2 interacts with CD81 in vitro. However, E2 interactions with LDLr and HCV interactions with CD81 have not been clearly described. Using sucrose gradient-purified low-density particles (1.03 to 1.07 g/cm 3 ), intermediate-density particles (1.12 to 1.18 g/cm 3 ), recombinant E2 protein, or control proteins, we assessed binding to MOLT-4 cells, foreskin fibroblasts, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
171
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(183 citation statements)
references
References 57 publications
11
171
0
1
Order By: Relevance
“…Molecular studies of HCV replication and infection have shown entry of the virus into the cell may occur via LDL and CD 81 receptors. [3][4][5] Binding and endocytosis of the virus is limited by LDL particles via competitive inhibition in vitro. 3 We evaluated the possibility of such inhibition in vivo and examined the influence of LDL levelson treatment outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular studies of HCV replication and infection have shown entry of the virus into the cell may occur via LDL and CD 81 receptors. [3][4][5] Binding and endocytosis of the virus is limited by LDL particles via competitive inhibition in vitro. 3 We evaluated the possibility of such inhibition in vivo and examined the influence of LDL levelson treatment outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Two molecules are proposed to function as HCV receptors, namely, the low-density lipoprotein receptor (LDLR) and CD81. [3][4][5] Experiments in vitro showed competitive inhibition of binding between HCV and LDLR by purified LDL. 3 If similar inhibition occurs in vivo, the serum concentration of beta-lipoproteins may influence HCV proliferation because cell infection is required for replication of the virus.…”
mentioning
confidence: 99%
“…The ability of E2 to bind to CD81 has been widely documented; however, widespread distribution of CD81 on nonpermissive cells (30) led to the view that other liver-specific molecules must also be involved in facilitating entry (19). Several other cell surface molecules have been reported to bind to native HCV particles or recombinant E2, including the low-density lipoprotein receptor (1,51), dendritic-cell-specific intercellular adhesion molecule 3-grabbing nonintegrin (DC-SIGN) and liver/lymph nodespecific intercellular adhesion molecule 3-grabbing integrin (L-SIGN or DC-SIGNR) (20,32,42), glycosaminoglycans (4), and scavenger receptor class B type I (SR-B1) (6,44). Despite early doubts about the function of CD81 in HCV entry, data using recently developed assays of retroviral pseudoparticles (HCVpp) and in vitro infectious clones support a central role for CD81 in mediating infection (6,11,29,31).…”
Section: Hepatitis C Virus (Hcv)mentioning
confidence: 99%
“…Tetraspanin CD81 has been well characterized as a major factor for HCV cellular entry (Bartosch et al, 2003;Buck, 2008;Cormier et al, 2004;Hsu et al, 2003;Kapadia et al, 2007;Koutsoudakis et al, 2007;Molina et al, 2008;Petracca et al, 2000;Pileri et al, 1998;Wunschmann et al, 2000; (Fig 1, step 3). E2 protein has been shown to exhibit a very high affinity (K d ~10 -9 M) for the large extracellular loop of CD81 (Petracca et al, 2000;Pileri et al, 1998).…”
Section: Hcv Cellular Entrymentioning
confidence: 99%